Determination of Phenanthrene and Naphthalene in the Loess Area by Synchronous Fluorimetry - Zhan, Huiying; Jiang, Yufeng (Asian Journal of Chemistry, 2013)
The synchronous flourimetry has been established for simultaneous determination of phenanthrene and naphthalene in the mixed liquor of these two components. The linear ranges of phenanthrene and naphthalene are 0.001-0.101 and 0.0025-0.25 mg/L, their detection limits are 0.47 and 0.14 ng/mL and their relative standard deviations are 0.48 and 0.89 %, (n = 12), respectively. The method could be used to study the simultaneous determination of phenanthrene and naphthalene in the upper clear liquor after the sorption equilibrium of the loess soils on the mixed liquor. The results show that the sorption isotherm of natural loess soils on phenanthrene and naphthalene satisfies Freundlich-Equation and provided a fast and simple way to forecast and govern pollution of soils.